Feeding Wild Birds in America : Culture, Commerce, and Conservation - Baicich, Paul J.; Henderson, Carrol L.; Barker, Margaret A. (Book collections on Project MUSE., 2014)
Today, according to the US Fish and Wildlife Service, more than fifty million Americans feed birds around their homes, and over the last sixty years, billions of pounds of birdseed have filled millions of feeders in backyards everywhere. Feeding Wild Birds in America tells why and how a modest act of provision has become such a pervasive, popular, and often passionate aspect of people's lives. Each chapter provides details on one or more bird-feeding development or trend including the "discovery" of seeds, the invention of different kinds of feeders, and the creation of new companies. Also wov.